Interleaved binomial kT‐points for water‐selective imaging at 7T. Issue 6 (9th August 2022) - Löwen, Daniel; Pracht, Eberhard D.; Stirnberg, Rüdiger; Liebig, Patrick; Stöcker, Tony
Abstract : Purpose: We present a time‐efficient water‐selective, parallel transmit RF excitation pulse design for ultra‐high field applications. Methods: The proposed pulse design method achieves flip angle homogenization at ultra‐high fields by employing spatially nonselective k T $$ {k}_T $$ ‐points pulses. In order to introduce water‐selection, the concept of binomial pulses is applied. Due to the composite nature of k T $$ {k}_T $$ ‐points, the pulse can be split into multiple binomial subpulse blocks shorter than half the precession period of fat, that are played out successively. Additional fat precession turns, that would otherwise impair the spectral response, can thus be avoided. Bloch simulations of the proposed interleaved binomial k T $$ {k}_T $$ ‐points pulses were carried out and compared in terms of duration, homogeneity, fat suppression and pulse energy. For validation, in vivo MP‐RAGE and 3D‐EPI data were acquired. Results: Simulation results show that interleaved binomial k T $$ {k}_T $$ ‐points pulses achieve shorter total pulse durations, improved flip angle homogeneity and more robust fat suppression compared to available methods. Interleaved binomial k T $$ {k}_T $$ ‐points can be customized by changing the number of k T $$ {k}_T $$ ‐points, the subpulse duration and the order of the binomial pulse. Using shorter subpulses, the number of k T $$ {k}_T $$ ‐points can be increased and hence better homogeneity is achieved, while still maintaining short total pulse durations. Flip angle homogenization and fat suppression of interleaved binomial k T $$ {k}_T $$ ‐points pulses is demonstrated in vivo at 7T, confirming Bloch simulation results. Conclusion: In this work, we present a time efficient and robust parallel transmission technique for nonselective water excitation with simultaneous flip angle homogenization at ultra‐high field.